Microbiological Quality Analysis of Dried Anchories (Stelophorus heterolubus) in Toniku Village, West Halmahera Regency - Ruslan A. Daeng; Kusdi Hi. Iksan (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study aims to assess the microbiological quality of dried anchovies in Toniku Village, West Halmahera, to ensure product safety and quality before distribution. The production of anchovies in Indonesia has shown a rapid increase; however, inadequate sanitary handling and storage practices can promote the growth of harmful microorganisms. The research involved sampling dried anchovies and conducting microbiological tests in the laboratory, focusing on key parameters such as the Total Plate Count (TPC), presence of Escherichia coli, and Salmonella. Results showed that TPC values increased with storage time, reaching the highest level after three months. Additionally, tests for pathogenic microorganisms indicated negative results for E. coli and Salmonella, suggesting satisfactory hygiene during processing. The processing stages, including raw material selection, blanching, and careful drying, play a crucial role in preventing microbial contamination. These findings suggest that the dried anchovies from Toniku are still within safe limits and suitable for consumption, although microbial growth during storage warrants attention. The study concludes that maintaining good sanitation practices and quality control during processing is essential to preserve microbiological quality and ensure consumer safety.